Validity and reliability test of screening questionnaires training movement appropriate to elderly people - Cerika Rismayanthi (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2020)
Increased age experienced by each person will end with the elderly age group, which is vulnerable to various activities due to physiological function decrease occurred. On the other hand, the elderly need to stay alive. Instead of socio-psychological aspects, muscular function, cardiovascular and balance, and mobility aspects are important factors that support our body's work. The assessment in this study uses the questionnaire of